ASSESSMENT OF ANTIMICROBIAL EFFICACY OF KOHL/KAJAL PREPARED BY DIFFERENT INDIAN METHODS AGAINST SELECTED MICROBIAL STRAINS - RANDIVE, DHEERAJ S.; BHINGE, SOMNATH D.; JADHAV, NAMDEO R.; BHUTKAR, MANGESH A.; SHIRSAT, MRUNAL K. (International Journal of Current Pharmaceutical Research, 2020)
Objective: To prepare and evaluate different types of Kajal formulations and evaluation of its antimicrobial activity along with preliminary verification of the content responsible for the said effect. Methods: We have prepared kajal formulations by use of different metal plates, marble tile, ghee and Aloe vera mucilage and tried to verify the antimicrobial effect attributed to the formulation by these substances. Results: Carbon soot obtained from the use of copper plate showed more antimicrobial potential against Staphylococcus aureus, Pseudomonas aeruginosa and E. coli, with zones of inhibition 18±0.235 mm, 17±0.124 mm and 19±0.528 mm respectively. Also this formulation at different concentrations when compared with Ciprofloxacin exhibited promising results. Moreover, this formulation when used with Ciprofloxacin at a concentration of (50:50) revealed a synergistic effect against the clinically resistant strains of P. aeruginosa, with zone of inhibition 22±0.578 mm and 20±0.987 mm at a concentration of 10 and 5 µg ml-1 respectively, whereas, Ciprofloxacin exhibited zone of inhibition of 26±0.457 mm and 24±0.751 mm at the similar concentrations. To assess the effectiveness of Aloe vera we used marbles tiles for collection of carbon soot. The zones of inhibition observed for Kohl formulations prepared by using carbon soot collected from marble tiles impregnated with Aloe vera mucilage exhibited less antimicrobial activity than that of copper soot against the selected microbial strains. Conclusion: All the prepared kajal formulations exhibited antimicrobial activity. Aloe vera and copper soot is responsible for significant antimicrobial activity and when combined with Ciprofloxacin it showed synergistic activity against the clinically resistant strains of P. aeruginosa.